Investigating EFL undergraduates vocabulary learning strategies (VLSs) at a university in Syria - Daaboulis, Maisaa Moustafa; Nimehchisalem, Vahid; Jubier, Mustafa Mahdi (2018)
Although vocabulary learning plays a significant role in developing learners’ abilities to understand and use a language for communication, there is little research conducted on vocabulary learning among EFL Syrian learners. Therefore, the present study aims to investigate the use of Vocabulary Learning Strategies (VLSs) among 100 randomly selected EFL Syrian first-year undergraduates in a university in Syria. Using quantitative methods of data collection and analysis, the data were collected through the VLS questionnaire. Descriptive statistics was used to analyze the data. The results showed that the EFL Syrian learners are moderate users of VLSs. The results also demonstrated that direct memory applying strategies scored the highest mean value among the ten categories of VLSs, while indirect cognitive creative strategies indicated the lowest mean value. It was concluded therefore that the average EFL Syrian undergraduate needs more training on vocabulary learning, especially on the use of VLSs and expanding their vocabulary knowledge.